Innovative Financing for Development - Ketkar, Suhas (Washington, DC : World Bank, 2012)
In the run-up to the 'follow-up international conference on financing for development' to be held in Doha from November 28 to December 2, 2008, it seems particularly timely to collect in one book writings on the various market-based innovative methods of raising development finance. Although developing countries are well advised to use caution in incurring large foreign debt obligations, especially of short duration, there is little doubt that poor countries can benefit from cross-border capital whether channeled through the public or private sectors. The papers in this book focus on various recent innovations in international finance that allow developing countries to tap global capital markets in times of low risk appetite, thereby reducing their vulnerability to booms and busts in capital flows. Debt issues backed by future hard currency receivables and diaspora bonds fall into the category of mechanisms that are best described as foul-weather friends. By linking the rate on interest to a country's ability to pay, Gross Domestic Product (GDP)-indexed bonds reduce the cyclical vulnerabilities of developing countries. Furthermore, these innovative mechanisms perm lower-cost and longer-term borrowings in international capital markets. Not only do the papers included in this book describe the innovative financing mechanisms; they also quantify the mechanisms' potential size and then identify the constraints on their use. Finally, the papers recommend concrete measures that the World Bank and other regional development banks can implement to alleviate these constraints. Economists have analyzed the feasibility and potential of using various tax-based sources of development finance in the context of meeting the millennium development goals. This has given rise to a new discipline of global public finance. This book complements those efforts by focusing on market based mechanisms for raising development finance.